2000
DOI: 10.1016/s0014-5793(00)01795-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of melanogenesis by vacuolar type H+‐ATPase inhibitors in amelanotic, tyrosinase positive human and mouse melanoma cells

Abstract: In this study, we describe the activation of melanogenesis by selective vacuolar type H + -ATPase inhibitors (bafilomycin A1 and concanamycin A) in amelanotic human and mouse melanoma cells which express tyrosinase but show no melanogenesis. Addition of the inhibitors activated tyrosinase within 4 h, and by 24 h the cells contained measurable amounts of melanin. These effects were not inhibited by cycloheximide (2 W Wg/ml) which is consistent with a post-translational mechanism of activation. Our findings sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 34 publications
6
34
0
Order By: Relevance
“…Our results are in agreement with previous reports demonstrating that melanin synthesis was stimulated by agents that increase melanosome pH. This is true for the lysosomotropic compound, ammonium chloride, ionophores such as nigericin and monensin, and inhibitors of the vacuolar ATPases such as bafilomycin (26,27). Fuller et al (28) reported that the melanosomes of melanocytes from Caucasian skin displayed low tyrosinase activity and were more acidic than the melanosomes of melanocytes from black skin, which had high tyrosinase activity.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with previous reports demonstrating that melanin synthesis was stimulated by agents that increase melanosome pH. This is true for the lysosomotropic compound, ammonium chloride, ionophores such as nigericin and monensin, and inhibitors of the vacuolar ATPases such as bafilomycin (26,27). Fuller et al (28) reported that the melanosomes of melanocytes from Caucasian skin displayed low tyrosinase activity and were more acidic than the melanosomes of melanocytes from black skin, which had high tyrosinase activity.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, melanosomes and lysosomes contain many of the same structural proteins (e.g. LAMP, acidic hydrolases, vacuolar-type proton pumps (47,74,75)), and both are affected in several genetic disorders, such as the Chediak-Higashi and Hermansky-Pudlak syndromes (76,77). The catalytic domains of TYR and other enzymes involved in melanogenesis are located within the lumen of the melanosome, and it follows that their activity is likely to be dependent upon the intramelanosomal environment, including the pH (19).…”
Section: Discussionmentioning
confidence: 99%
“…It has been assumed that this low melanosomal pH facilitates melanogenesis (44 -46). Recently, the activation of melanogenesis by selective vacuolar type proton pump inhibitors, bafilomycin A1 (Baf) and concanamycin A (CCM), was shown in amelanotic human melanoma cells and in mouse melanoma cells, which express TYR but do not produce pigment (47). Further, Baf and CCM induce melanin synthesis in pink-eyed dilution gene (p)-null melanocytes by affecting early TYR processing and trafficking rather than by simply affecting activity at the melanosomal level (48,49).…”
mentioning
confidence: 99%
“…Tyrosinase, the rate-limiting enzyme in melanogenesis, exhibits optimal enzymatic activity at neutral pH but is almost completely inactive at acidic pH (Hearing and Ekel 1976;Ancans et al 2001b). Further, selective V-ATPase inhibitors (bafilomycin A1 and concanamycin A) or ionophores that dissipate the proton gradient stimulate melanogenesis Oikawa 1983, 1985;Oikawa et al 1987;Ancans and Thody 2000;Halaban et al 2002;, implying an anti-melanogenic role for luminal acidification. These observations indicate that the acidification inside melanosomes is inhibitory for melanogenesis (Ancans et al 2001a(Ancans et al , 2001b.…”
Section: Introductionmentioning
confidence: 99%